Aerodynamic Performances of MAV Wing Shapes / N. I. Ismail...[et al.] - N. I., Ismail; A. H., Zulkifli; H., Yusoff; R. J., Talib; A.R., Hemdi; N. Mustapa, N. M. Muzammil (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
In general, there are four common Low Reynolds Number wing's designs for fixed wing Micro Air Vehicle (MAV) which known as Rectangular, Zimmerman, Inverse Zimmerman and Ellipse wing. However, each wing design produces diverse performance and in fact the aerodynamic comparison study among the wings is still lack. Thus, the objective of this study is to evaluate the basic aerodynamic performance found on Rectangular, Zimmerman, Inverse Zimmerman and Ellipse wing designs with view to find the optimal wing shape for Micro Air Vehicle (MAV) configuration. Here, each design was analysed based on simulation works. The results show that at stall angle, the Ellipse wing has maximum lift coefficient ( ) recorded at 1.12 which is at least 4.33% higher than the other wing designs. Based on drag coefficient ( ) analysis, the Inverse Zimmerman Wing exhibited the lowest minimum drag value at 0.033 which is 8.45% lower than the other wing's designs. In moment coefficient analysis, the results reveal that the Inverse Zimmerman Wing has produced the steepest curve slope value at -0.36 which is 17.39% higher than the other wings. The aerodynamic efficiency ( ⁄) study has also revealed that Zimmerman Wing recorded the highest ⁄value at 6.80 and at least 1.35% higher than to the other wing. Based on these results, it was concluded that Zimmerman wing has the highest potential to be adopted as MAV wing due to its optimal aerodynamic efficiency.